Influence of territorial distribution on verbal-visual advertisements - Lyubomira Spasova (Business & Management Compass)
The study of verbal-visual cognitive styles of advertising of consumers is a new scientific study that aims to prove that cognitive affiliation is a determinant of successful advertising communication. The present scientific work aims to distribute the consumers of advertising according to the scale of Kirby et al. (1988), as well as according to their territorial distribution. Consumers from Asian countries are formed as high verbalizers and consumers from European countries as high visualizers. Users from the Balkan countries have high values on the Dreams subscale. Through correlation dependences, it is established that high verbalization is positively related to short verbal structures, and high visualization - to color brightness in advertising. These generalizations confirmed the empirical evidence from other studies, because the verbal orientation of Asian-type consumers facilitates the understanding of advertising messages reflecting their cultural values, and the visual structures in advertising facilitate the perception of European-type consumers. The scientific findings would be useful for advertisers, marketers and advertising researchers.